2018
DOI: 10.1200/jgo.18.41300
|View full text |Cite
|
Sign up to set email alerts
|

Loss to Follow-Up in a Cervical Cancer Screening and Treatment Program in Western Kenya

Abstract: Background: Increasingly, evidence is emerging from developing countries like Kenya on the burden of loss to follow-up care after a positive cervical cancer screening/diagnosis, which impacts negatively on cervical cancer prevention and control. Unfortunately little or no information exists on the subject in the western region of Kenya. This study is designed to determine the proportion of and predictors and reasons for defaulting from follow-up care after positive cervical cancer screen. Aim: To determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Our treatment uptake rate of 52%, while lower than reported rates in the two studies using the Xpert HPV assay, is comparable to rates of follow‐up reported in VIA‐based programs in similar settings 14,20. However, studies show that HPV‐based screening, recommended as first‐line in LMICs where available, is more effective than VIA‐based screening,21 and has greater reduction in mortality from cervical cancer when coupled with treatment compared to VIA 5.…”
Section: Discussionsupporting
confidence: 44%
“…Our treatment uptake rate of 52%, while lower than reported rates in the two studies using the Xpert HPV assay, is comparable to rates of follow‐up reported in VIA‐based programs in similar settings 14,20. However, studies show that HPV‐based screening, recommended as first‐line in LMICs where available, is more effective than VIA‐based screening,21 and has greater reduction in mortality from cervical cancer when coupled with treatment compared to VIA 5.…”
Section: Discussionsupporting
confidence: 44%
“…12 However, there still remain challenges in getting treatment to those with positive tests. 13,14 Women often need to travel great distances to facilities for treatment, resulting in substantial defaulting and failure to receive therapy. 11 To address the public health problem of cervical cancer in sub-Saharan Africa, we sought to take advantage of the technologic advancements in HPV testing and couple them with practical insights (eg, mobile treatment provision) to develop a community-based "public health approach" to screening.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding treatment, the World Health Organization recommends ablative therapy for a positive HPV result without further diagnostic confirmation 12 . However, there still remain challenges in getting treatment to those with positive tests 13,14 . Women often need to travel great distances to facilities for treatment, resulting in substantial defaulting and failure to receive therapy 11 …”
Section: Introductionmentioning
confidence: 99%
“… 4 LTFU in cancer care remains a challenge, as is the case in most lower- and middle-income countries. 7 One third of our participants could not be accounted for after the first visit. Contributing factors to high LTFU could not be established in this study, but unreported deaths, low socioeconomic status, low education levels, lack of adequate patient education, and higher levels of alternative medicine use are among the reasons cited in other sources.…”
Section: Discussionmentioning
confidence: 99%